Science Teacher Professional Development Program through Lesson Study: Case of Thailand Demonstration School - Maneelam, Pratuengsook (Asia Research Network Journal of Education, 2022)
The paper aimed to clarify science teacher professional development program through lesson study in case of Khon Kaen University Demonstration Secondary School. The lesson study professional development program was proposed based on a specific Thailand school context – a university demonstration school. Methodology regarded qualitative research. Participants included 3 school administrators and 12 school science teachers who were working at Khon Kaen University Demonstration Secondary School, academic year of 2017. The participant was active in making informed decisions throughout all aspects of the research process for the primary purpose of imparting school social change; a specific action for proposing the lesson study professional development program. The tools of interpretation included the methods and techniques of observing and documenting. Data was analyzed and interpreted to find characteristics, patterns, attributes, and meanings of school science teachers’ collaboratively working for enhancing students’ learning. The findings revealed the proposed lesson study professional development program. The PD program highlighted what should be taken into account for community learning environment in order to enhance the university demonstration school science teachers to find a specific characteristic and collaboration, the pedagogical approach underlying the research lesson, and the development of studies on teaching and learning processes related to the research lesson.